Pubertal timing in children with Silver Russell syndrome compared to those born small for gestational age - Patti, Giuseppa; Malerba, Federica; Calevo, Maria Grazia; Schiavone, Maurizio; Scaglione, Marco; Casalini, Emilio; Russo, Silvia; Fava, Daniela; Bassi, Marta; Napoli, Flavia; Allegri, Anna Elsa Maria; D’Annunzio, Giuseppe; et al. (Frontiers in Endocrinology, 2022)
Context: Data on pubertal timing in Silver Russell syndrome (SRS) are limited. Design and Methods: Retrospective observational study including twenty-three SRS patients [11p15 loss of methylation, (11p15 LOM, n=10) and maternal uniparental disomy of chromosome 7 (mUPD7, n=13)] and 21 small for gestational age (SGA). Clinical (thelarche in females; testis volume ≥ 4 ml in males; pubarche), BMI SD trend from the age of 5 to 9 years to the time of puberty, biochemical parameters of puberty onset [Luteinizing hormone (LH), 17-β-estradiol, testosterone], and bone age progression were evaluated Results: Pubertal onset and pubarche occurred significantly earlier in children with SRS than in SGA (p 0.03 and p 0.001, respectively) and clinical signs of puberty onset occurred earlier in mUPD7 than in 11p15LOM group (p 0.003). Five SRS children experienced central precocious puberty and LH, 17-β-estradiol, testosterone were detected earlier in SRS than in SGA (p 0.01; p 0.0001). Bone age delay in SRS children was followed by rapid advancement; the delta between bone age and chronological age in SRS group became significantly higher than in SGA group at the age of 9-11 years (p 0.007). 11p15LOM patients were underweight at the age of 5 years and showed a progressive normalization of BMI that was significantly higher than in mUPD7 (p 0.04) and SGA groups (p 0.03) at puberty onset. Conclusion: Timing of puberty is affected in SRS and occurred earlier in mUPD7 compared to 11p15LOM. The impact of early puberty on adult height and metabolic status deserves long-term evaluation.